NATIONAL ROAD PRESERVATION BASED ON IRMS METHOD (A CASE STUDY IN JAPURA – PEMATANG REBA IN RIAU PROVINCE) - Benny Hamdi Rhoma Putra; Yosi Alwinda; M. Rilly Aka Yogie (Jurnal Pensil : Pendidikan Teknik Sipil, 2022)
Japura Airport is one of the nodes of transportation that owned by Inderagiri Hulu (Inhu) Regency. The airport is located 14 km from the Pematang Reba. Pematang Reba is public administration office complex in Inhu Regency. This airport has flights within the province and even flights between provinces adjacent to Riau Province. The road that separates of these two cities is considered as the economic lifeblood of Inhu Regency to Riau Province. In addition, this road has fungtion not only to connect two important locations in Inhu Regency but also as only road access from Riau Province to Jambi Province. Because of the importance of this road, the condition of this road must be always maintained. Through this study, an analysis of the Remaining Structural Life (RSL) of the pavement was carried out to determine the most appropriate recommendations for road preservation work. The IRMS method is the method which used in calculating the remaining structural life (RSL) of the flexible pavement. The data requairement are deflection data from the Falling Weight Deflectometer (FWD), road geometric condition data and Average Daily Traffic (ADT). Through calculations, it was found that the apropriate flexible pavement preservation programs for Jalan Japura to Pematang Reba were divided into 3 types. Firstly, Overlays program are needed for STA 3+ 393 to STA 7+712, STA 8+509 to STA 15+70 and STA 16+510 to 16+819. Secondly, segment from STA 7+930 to STA 8+ 312 needs Reconstruction. Thirdly, STA 15+922 to STA 16+303 needs routine maintenance.